Sound propagation in urban canyons: a case study of simulation reliability. Issue 4 (4th July 2019) - Engedy, Anna Eszter; Lechleitner, Josef; Mahdavi, Ardeshir
Abstract : Problems associated with increased urban noise exposure – especially due to road traffic – are well known. However, the acoustic planning of urban areas and the potential of simulation still does not receive sufficient attention. In this context, the present contribution focuses on urban canyons via comparison of measured and simulated sound levels. Toward this end, a room acoustic simulation tool was deployed to model two areas in the city of Vienna. Simulation results were shown to generally agree with the measurements. The contribution includes also a sensitivity analysis to explore the impact of variations in model assumptions on simulation results.